Cav1.2, Cell Proliferation, and New Target in Atherosclerosis. (12th May 2013) - Soldatov, Nikolai M.
Abstract : C a v 1.2 calcium channels are the principal proteins involved in electrical, mechanical, and/or signaling functions of the cell. C a v 1.2 couples membrane depolarization to the transient increase in intracellular Ca 2+ concentration that is a trigger for muscle contraction and CREB-dependent transcriptional activation. The CACNA1C gene coding for the C a v 1.2 pore-forming α 1 C subunit is subject to extensive alternative splicing. This review is the first attempt to follow the association between cell proliferation, C a v 1.2 expression and splice variation, and atherosclerosis. Based on insights into the association between the atherosclerosis-induced molecular remodeling of C a v 1.2, proliferation of vascular smooth muscle cells, and CREB-dependent transcriptional signaling, this review will give a perspective outlook for the use of the CACNA1C exon skipping as a new potential gene therapy approach to atherosclerosis.